Lived Experiences of English Teachers who were Initially Taught English in Nepali: Implications for Professional Development Programmes - Lamichhane, Bhogendra (Innovative Research Journal, 2023)
This research explores the perspectives of current English teachers in Nepal who were initially taught English in Nepali. The study adopts a qualitative approach, utilizing semi-structured interviews and thematic analysis to uncover key factors influencing their preferences and challenges in English language instruction. The research reveals the impact of traditional teaching methods, such as rote learning, on their language proficiency, but also highlights teachers who embrace interactive and student-centered approaches. Challenges in conveying idiomatic expressions and cultural nuances are evident, influenced by prior knowledge of Nepali language structures. The teachers' adaptations include differentiated instruction and experiential learning, emphasizing the importance of continuing professional development. The findings contribute to the development of targeted professional development programmes to enhance English education in Nepal and create a supportive learning environment.